Menyingkap Fungsi Sosial Perbankan Syariah Dan Pengaruhnya Terhadap Kinerja Keuangan - Sulhani Sulhani; Abdul Mughni (LPPM ISNJ Bengkalis, 2022)
The social function of Islamic banking is an essential factor in the existence of Islamic banking, and research is still lacking. This study aims to analyze the trend of the social function of Islamic banking, its reporting conformity with accounting standards, and its effect on the financial performance of Islamic banking. The population of this study is Islamic Commercial Banks (ICB) registered with the Financial Services Authority (FSA) from 2014-2019. The sampling technique used purposive sampling and obtained 59 samples. The method of analysis used descriptive analysis and multiple linear regressions. The results show that fines and non-halal income still dominate the social function instrument. Social functions such as zakat, infaq, alms, and waqf tend to be low. Social reports in the form of sources and uses of zakat funds are sufficient. Reports on sources and uses of benevolent funds are also in the sufficient category, but the percentage value is lower. Internal zakat positively affects the performance of Islamic banking as measured by Return on Assets (ROA) and Operating Expenses on Operating Income (BOPO). Other variables do not affect the performance of Islamic banking as measured by ROA, BOPO, and Non-Performing Financing (NPF). This research theoretically confirms that internal zakat can encourage the growth of Islamic banking. Islamic banking must pay attention to social functions, especially zakat, an order from Islam.